2020
DOI: 10.48550/arxiv.2008.09950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weak cosmic censorship conjecture is not violated for a rotating linear dilaton black hole

Fei Qu,
Si-Jiang Yang,
Zhi Wang
et al.

Abstract: In this paper, we investigate the validity of the weak cosmic censorship conjecture(WCCC) for a rotating linear dilaton black hole from two different methods. By using the classsical ingoing test particle method, we obtain the same results as given in the new version of gedanken experiment recently proposed by Wald. We find that even for this rotating linear dilaton black hole the Iyer-Wald formalism is still functioning. By comparing these two methods, we find that the same result will be obtained in both cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Recently, by taking into account the second-order perturbations that comes from the matter fields, Sorce and Wald showed that the Kerr-Newman black hole cannot be destroyed [34]. Subsequent systematic works further support the result that the event horizon cannot be destroyed by this kind of gedanken experiment [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 94%
“…Recently, by taking into account the second-order perturbations that comes from the matter fields, Sorce and Wald showed that the Kerr-Newman black hole cannot be destroyed [34]. Subsequent systematic works further support the result that the event horizon cannot be destroyed by this kind of gedanken experiment [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 94%
“…Recently, a possible connection between weak cosmic censorship conjecture (WCCC) [1][2][3][4][5][6] and weak gravity conjecture (WGC) [7][8][9] was proposed in [10]. It is the statement that if the weak gravity conjecture holds, a class of counterexamples [11] to cosmic censorship in Einstein-Maxwell theory with negative cosmological constant can be removed.…”
Section: Introductionsmentioning
confidence: 99%
“…They demonstrated that the event horizons of these black holes can be destroyed by test particles, and claimed that the destruction of such event horizons might provide us the possibility to access regions inside black hole event horizons [14]. However, using the new version of gedanken experiment proposed by Sorce and Wald [15], when the second-order approximation of the perturbation that comes from the matter fields is taken into account, Jiang and Gao showed that a static charged regular black hole coupled to nonlinear electromagnetical field cannot be overcharged [16], and many works have been done to destroy the event horizons of black holes using this new version of gedanken experiment [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%